PUBLIC HEALTH as a medical specialty in the European Union (Part 1) - Wdowiak, Leszek; Kapka, Lucyna (Polish Journal of Public Health, 2009)
At present, the medical specialty of public health is strengthening its position in the EU medical specialist system. According to the present EU decisions, the specialty of public health is automatically recognized in all EU countries. Competencies of a medical specialist in public health trained in one of the countries of the EU, European Economic Area and Switzerland, are recognized in all countries. It is justifi able, therefore, that the qualifi cations of medical specialists in public health in Poland are treated as equivalent to ‘community medicine’ in other European countries. In this respect, the adaptation of Directive 2005/36/EC to national conditions should be amended without delay, because the only equivalent of ‘community medicine’ is specialisation in public health. However, there is no consistency concerning the programmes of specialisation and terminology pertaining to public health, and also the lack of standardisation of terms in this fi eld. The Public Health Section of the European Union of Medical Specialists has been involved in the process of harmonization and maintaining of the high quality of specialist medical training and practice in public health in the EU countries, and has published the Recommendations to the UEMS Management Council and to the National Authorities (responsible for training in the speciality in public health in each member country) to assist in defi ning the competencies of specialists in public health in Europe. If the Member States wish to realise the assumed health strategies, then public health, as a discipline on the border of medicine and other sciences, would be a decisive leading area for actions conditioning the achievement of the desired goals. The medical profession engaged in the work in the area of public health faces great challenges concerning the harmonization and adaptation of this medical speciality on the European scale.